2019
DOI: 10.1186/s12884-019-2497-y
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone and misoprostol versus misoprostol alone for uterine evacuation after early pregnancy failure: study protocol for a randomized double blinded placebo-controlled comparison (Triple M Trial)

Abstract: BackgroundEarly pregnancy failure (EPF) is a common complication of pregnancy. If women do not abort spontaneously, they will undergo medical or surgical treatment in order to remove the products of conception from the uterus. Curettage, although highly effective, is associated with a risk of complications; medical treatment with misoprostol is a safe and less expensive alternative. Unfortunately, after 1 week of expectant management in case of EPF, medical treatment with misoprostol has a complete evacuation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…A Data Safety Monitoring Board oversaw the study and assessed the results of the interim analysis after 50% of inclusions regarding primarily effectivity and secondarily safety. A pre-defined stopping rule, according to O'Brien-Fleming, was used to assess the primary outcome, complete evacuation after 6À8 weeks [24]. Following this stopping rule, when analysis of the primary outcome would show a difference between both study groups with a p-value <0.0054, a premature halt of the trial would be justified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Data Safety Monitoring Board oversaw the study and assessed the results of the interim analysis after 50% of inclusions regarding primarily effectivity and secondarily safety. A pre-defined stopping rule, according to O'Brien-Fleming, was used to assess the primary outcome, complete evacuation after 6À8 weeks [24]. Following this stopping rule, when analysis of the primary outcome would show a difference between both study groups with a p-value <0.0054, a premature halt of the trial would be justified.…”
Section: Discussionmentioning
confidence: 99%
“…The study protocol is available from https://doi.org/10.1186/s12884À019À2497-y. 24 This trial was registered at the following registers: Clinicaltrials.gov: NCT03212352. Trialregister.nl: Trial NL 6366 EudraCT number: 2017-002694-19.…”
Section: Methodsmentioning
confidence: 99%
“…This economic evaluation was performed alongside the Triple M Trial, a nationwide multicentre double-blinded placebo-controlled RCT conducted in 17 Dutch hospitals [ 16 ]. A CONSORT checklist and further details about study design, sample size calculation, study procedures and outcome have been described previously [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, medical treatment has emerged and been pursued by both healthcare providers and patients to minimize the complications of surgical interventions. [ 6 , 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, medical treatment has emerged and been pursued by both healthcare providers and patients to minimize the complications of surgical interventions. [6,10,11] Medical management using misoprostol with or without mifepristone for early pregnancy failure has been examined by several studies and demonstrated to be safe and effective, with success rates ranging between 50% and 96.5%, [12][13][14] even in women with previous cesarean section. [15] A recent study suggested that a previous cesarean section (odds ratio [OR]: 5.15, 95% confidence interval [CI]: 1.15-23.05, P = .032) was a significant predictor for incomplete miscarriage.…”
Section: Introductionmentioning
confidence: 99%